(untitled) (Baghdad Science Journal, 2020)
This paper presents a sight about the chemical structure deformation of poly (ethylene-co-vinyl acetate) (EVA) samples according to the change ratio of rate constant values. Spectroscopy kinetics fluorescence curves are fitted for two characteristic wavelength domains of fluorescent intensities. The short wavelengths (320-400 nm) domain show spectra overlapping, while at long wavelengths (400-800 nm) domain spectra are arranged in regular for each specific accelerated aging time. The ratio of kinetics rate constant at long wavelengths to kinetics rate constant of short wavelengths is the criterion of the degree chemical structure deformation. Molar extrinsic coefficient relies on the chemical structure change. Through absorbance measurement, EVA samples have been classified into two groups. Presence of Cyasorb additive is the key point of the ranking. The effect of three different accelerated aging of dry (115 oC), damp (85% moisture, 85 oC), and irradiated (UV, 65 oC) aging have been considered for two samples of each group over different aging time. Spectroscopy of absorbance and fluorescent for aged samples have been discussed. In general, Cyasorb adding causes higher chemical structure deformation for the EVA sample. The most effective factor is the damp aging and the less one is the UV irradiation aging, while the biggest chemical structure change of Cyasorb-free sample is produced by damp aging and the less by dry heat.